Technology Entrepreneurship Project (ENT 600) : Top Glove Corporation Berhad / Nadzratul Aufa Mohd Faisal - Mohd Faisal, Nadzratul Aufa Mohd Faisal (2021)
The world's largest glove manufacturer is Top Glove Corporation Berhad. Malaysia is where the company's manufacturing operations are located. The focus of this report is on Top Glove's medical gloves, which will be identified and analysed in this company analysis. Latex allergy is a problem associated with medical gloves. So, in order to solve the problem, a solution is required. The solution that provides is mangosteen peel are mixing with natural rubber latex. This is due to the presence of xanthones in mangosteen peel, which have biological effects such as anti-allergy, antibacterial, and anti-viral. It aids in the treatment of skin allergies caused by latex protein. As a result, it is a viable option for preventing skin infection.